(Palestinian in the bodies of parliamentary Jordan in (1950-1967 - Alqam, Sami Mohammed (Journal of Humanities & Social Sciences, 2019)
After the Arab-Israeli war in 1948 and the establishment of the State of Israel on the Arab-Palestinian land، and the displacement of the Palestinian people to a number of Arab countries، foremost of which is Jordan. The Jordanian Arab Army، which participated in military operations in defense of Palestine، played a key role in rescuing the eastern and central parts of the country، which were later known as the West Bank of the Kingdom، including East Jerusalem. The unity between the banks of East and West Jordan gained its constitutional legitimacy by its approval and approval by the Jordanian Parliament on April 24، 1950. The Jordanian leadership was keen on the unity of the two people.
Keywords: Palestine; Jordan; parliamentary bodies; the constitution